(untitled) (Revista cientifica In Vestigium Ire, 2021)
This research work aimed to perform a productivity and efficiency analysis based on ISO 14001 and the life cycle analysis (LCA), which has been applied to obtain strategies for minimizing the environmental impacts generated by the company A&H Ingeniería y Construcciones SAS. To do this, the normative process of environmental impact assessment, for the entire productive chain of an organization, has been followed. In terms of efficiency, different economic concepts have proposed aspects that seek to promote economic growth and mitigate environmental impact, leading to meet the objectives set in the sustainable plan. Therefore, an economic evaluation has been made, using consumption and production data, for the Hitachi 450 LC Excavator, Model 2002. As a result of this study, it was obtained that the efficiency of the aforementioned machine is 60 % in the global effectiveness scale of the machine, based on the standards of availability, quality and performance index. Subsequently, the machine is classified as Unacceptable, meaning that it is generating significant losses and low competitiveness. For that reason, it is recommended to change its engine to generate greater profitability and less impact of polluting emissions to the environment.